THE TRANSFORMATION OF BUSINESS PROCESSES IN CONDITIONS OF DIGITALIZATION OF ECONOMIC SYSTEMS (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article considers to the aspects of identifying key directions that determine the successful functioning of an organization in the context of the digital economy development. The key areas of business transformation have been identified, allowing flexible restructuring of the company management process. Methods and techniques for assessing digital transformation in organizations that are tested for both quantitative and qualitative indicators have been considered. It has been proven that considering digital transformation is advisable not only in the context of studying business models in the development of digital technologies, but also from the point of view of what economic effects are achieved through digital transformation and how justified it.
Keywords: Key words: digital transformation, business model, digitalization, business management, methods.